Trends and Outcomes of Aortic Root Enlargement During Bioprosthetic Aortic Valve Replacement - Andre Y. Son, MD, MS; Abigail S. Baldridge, DrPH; Andrei Churyla, MD; Duc Thinh Pham, MD; Christopher K. Mehta, MD; Douglas R. Johnston, MD; Patrick M. McCarthy, MD; S. Christopher Malaisrie, MD (Annals of Thoracic Surgery Short Reports)
Background: Aortic root enlargement (ARE) during aortic valve replacement (AVR) mitigates prosthesis-patient mismatch, but its use has been low. Transcatheter aortic valve-in-valve (VIV) as a treatment for failing bioprosthetic valves is limited by small surgical valves, renewing interest in ARE during the index AVR. This study demonstrates trends and outcomes of ARE after commercial approval of VIV in 2015. Methods: This retrospective cohort study analyzed 2182 patients undergoing nonemergent AVR between August 2007 and December 2022. Endocarditis, aortic dissection, and concomitant root replacement or ventricular assist device placement were excluded. Trends in ARE use, valve size, and types were compared. Outcome measures included 30-day mortality and gradients and were compared between patients with and without ARE. Results: Overall, 74 patients (3.4%) underwent ARE, 14 (1.0%) before 2015 and 60 (7.6%, P < .0001) after 2015. Use of smaller valves (19-21 mm) decreased from 372 (26.8%) before 2015 to 85 (10.7%, P < .0001) after 2015. ARE group was younger than the AVR-alone group (64 vs 68 years, P = .001) but had similar predicted risk of mortality (median, 1.7%). Both groups had comparable postoperative mean gradients (ARE: 11 vs AVR-alone: 10 mm Hg, P = .42). ARE had higher 30-day mortality (5 [7%] vs 48 [2%], P = .014); however, no difference was found in elective patients (2 of 65 [3%] vs 39 of 1898 [2%], P = .57). Conclusions: ARE use has increased since commercial approval of VIV. The addition of ARE to AVR did not affect early safety in elective cases, and postoperative gradients were similar to those in patients not requiring ARE. Further studies are required to determine long-term outcomes after ARE, including VIV candidacy.